EFEITO EXPRESSIVO DAS VARIANTES ESTILÍSTICAS DO /r/ - Viola, Izabel Cristina (Intercâmbio, 2010)
This work discusses the stylistical uses of the /r/ variation orally expressed in the poem “I-Juca Pirama”. The variation can evolve as a dynamic unit in a continuum (from friction to vibration) by using a multiple alveolar trill and a glottal fricative when manifesting anger and sadness in the speech.